Neutron studies of the interaction of a cationic dye with carbon nanotubes and Laponite nanoplates in aqueous suspensions - Bulavin, L. A.; Savenko, V. S.; Lebovka, N. I.; Soloviev, D. V.; Ivankov, O. I.; Kuklin, O. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
The results of small-angle neutron scattering study of water – carbon nanotubes and water – carbon nanotubes – Laponite systems in the presence of synthetic dye methylene blue (MS) are presented. The concentrations of nanotubes and Laponite were stable and equal to 0.2 and 0.1% wt respectively. The concentration of methylene blue was varied in the range of (0.001–0.1)% wt. During the experiment, the temperature had a constant value of 293 K. It was established that the adding of Laponite improves the interaction of carbon nanotubes with MS.